Noncontrast Chest Computed Tomographic Imaging of Obesity and the Metabolic Syndrome: Part I Cardiovascular Findings. Issue 2 (March 2019) - Schlett, Christopher L.; Nattenmüller, Johanna; Tsuchiya, Nanae; Vogel-Claussen, Jens; Kauczor, Hans-Ulrich; Levin, David; Hatabu, Hiroto; Estépar, Jose R.; Wu, Ming-Ting; van Beek, Edwin J.R.; Schiebler, Mark L.
Abstract : There are physiological consequences of overeating that can lead to increased morbidity and mortality. The purpose of this review article is to acquaint the reader with the current state of the art in the non–cardiac-gated, noncontrast chest computed tomographic (NCCT) imaging biomarkers of the metabolic syndrome and their prognostic significance found in the lower neck and chest. NCCT imaging biomarkers associated with metabolic syndrome in the chest include premature coronary artery calcification, acceleration of large vessel arterial and valvular calcifications associated with atherosclerosis, and pulmonary arterial enlargement from pulmonary hypertension associated with sleep apnea. These easily identified imaging biomarkers have prognostic implications for major adverse cardiac events (MACE). These NCCT chest-imaging biomarkers are likely targets for artificial intelligence algorithms to harvest for longitudinal assessment of their individual and multifactorial contributions to chronic disease, MACE, and mortality. Early recognition and treatment of these common disorders may help improve patient outcomes and quality of life while decreasing medical costs. Abstract : Supplemental Digital Content is available in the text.